Role of interannual Kelvin wave propagations in the equatorial Atlantic on the Angola Benguela Current system. Issue 6 (8th June 2017) - Imbol Koungue, Rodrigue Anicet; Illig, Serena; Rouault, Mathieu
Abstract: The link between equatorial Atlantic Ocean variability and the coastal region of Angola‐Namibia is investigated at interannual time scales from 1998 to 2012. An index of equatorial Kelvin wave activity is defined based on Prediction and Research Moored Array in the Tropical Atlantic (PIRATA). Along the equator, results show a significant correlation between interannual PIRATA monthly dynamic height anomalies, altimetric monthly Sea Surface Height Anomalies (SSHA), and SSHA calculated with an Ocean Linear Model. This allows us to interpret PIRATA records in terms of equatorial Kelvin waves. Estimated phase speed of eastward propagations from PIRATA equatorial mooring remains in agreement with the linear theory, emphasizing the dominance of the second baroclinic mode. Systematic analysis of all strong interannual equatorial SSHA shows that they precede by 1–2 months extreme interannual Sea Surface Temperature Anomalies along the African coast, which confirms the hypothesis that major warm and cold events in the Angola‐Benguela current system are remotely forced by ocean atmosphere interactions in the equatorial Atlantic. Equatorial wave dynamics is at the origin of their developments. Wind anomalies in the Western Equatorial Atlantic force equatorial downwelling and upwelling Kelvin waves that propagate eastward along the equator and then poleward along the African coast triggering extreme warm and cold events, respectively. A proxy index based on linear ocean dynamics appears to be significantly more correlated with coastal variability than an index based on wind variability. Results show a seasonal phasing, with significantly higher correlations between our equatorial index and coastal SSTA in October–April season. Key Points: Interannual Equatorial Kelvin waves in the tropical Atlantic are linked to major warm and cold events in the Angola Benguela Current system Interannual Equatorial Kelvin waves at the origin of warm and cold events are well monitored by PIRATA moorings and altimetry An interannual Equatorial Kelvin wave index is a skillful proxy to forecast warm and cold events by about 1 month